Woody Allen a documentary - Cantelon, Paul 1959- (NFP Marketing, 2012)
Iconic writer, director, actor, comedian, and musician Woody Allen allowed his life and creative process to be documented on-camera for the first time. With this unprecedented access, Emmy-winning, Oscar-nominated filmmaker Robert Weide followed the notoriously private film legend over a year and a half to create the ultimate film biography. Exploring the ultimate "independent filmmaker's" writing habits, casting, directing, and relationship with his actors, Weide traveled with Allen from the London set of You Will Meet a Tall Dark Stranger - a major coup "considering Woody has never allowed so much as an EPK [Electronic Press Kit] crew on his sets," claims Weide - to the Cannes premiere of Midnight in Paris this May. He also filmed Allen at home, in the editing room and touring his childhood haunts in the Midwood section of Brooklyn. New interviews provide insight and backstory: actors Antonio Banderas, Josh Brolin, Penelope Cruz, John Cusack, Larry David, Seth Green, Mariel Hemingway, Scarlett Johansson, Julie Kavner, Diane Keaton, Martin Landau, Louise Lasser, Sean Penn, Tony Roberts, Chris Rock, Mira Sorvino, Naomi Watts, Dianne Wiest, and Owen Wilson; writing collaborators Marshall Brickman, Mickey Rose and Doug McGrath; cinematographers Gordon Willis and Vilmos Zsigmond; Allen's sister and producing partner Letty Aronson; producers Robert Greenhut and Stephen Tenenbaum; longtime managers Jack Rollins and Charles H. Joffe; casting director Juliet Taylor; pal Dick Cavett; and Martin Scorsese; among many others
Bildformat 1.78:1 (16:9)
Orig.: USA 2012
Enth. deleted scenes ; 12 Fragen an Woody Allen ; Interview mit Robert B. Weide
Keywords: Allen, Woody -- 1935-; Film; Biografie; DVD-Video